A dual-phase boride ceramic particle reinforced copper matrix composite material, a preparation method and application thereof
Patent Information
- Application Number
- CN202410429610.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-04-10
AI Technical Summary
纳米尺度的第二相与运动的位错相互作用使得复合材料的强度增加,但是耐磨性的提高则需要微米甚至毫米尺度的强化相来抵抗磨损,过分细小的强化相可能会在基体中发生团聚或者产生成分偏析,这将削弱复合材料的机械性能和摩擦磨损性能
[0021]This invention discloses a method for preparing a copper-based composite material reinforced with biphase boride ceramic particles. Low-speed, long-term rotation in a planetary ball mill coats the surface of the ceramic particles with metal powder, resulting in uniform mixing of the ceramic and metal powders. Wet mixing absorbs the heat generated during the ball milling process, preventing oxidation of the copper-titanium alloy powder and maintaining its high purity. Spark plasma sintering possesses the unique property of sintering powders under pressure. Furthermore, applying pressure during sintering helps lower the sintering temperature of the mixed powders, effectively preventing excessively coarse grains in the metal matrix during solid-phase sintering of the composite material. Solution treatment allows excess metal atoms to dissolve and distribute uniformly within the matrix, improving the strength of the copper matrix. Subsequent aging treatment causes supersaturated metal atoms to precipitate as a second phase within the matrix, increasing its conductivity. Electron beam remelting technology induces interfacial reactions between the ceramic particles and the copper matrix, aiming to achieve synergistic optimization of the surface microstructure.
Smart Images

Figure CN118326199B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of wear-resistant material preparation technology, specifically relating to a dual-phase boride ceramic particle reinforced copper-based composite material, its preparation method, and its application. Background Technology
[0002] Copper-based composites are widely used in electrical contact systems due to their excellent electrical conductivity, ease of processing, low cost, and good corrosion resistance. However, their low strength and poor wear resistance severely limit their applications. Currently, the strength and wear resistance of composites can be improved through precipitation strengthening and sedimentation strengthening, and the intrinsic properties of the reinforcing phase have a significant impact on the overall characteristics of the composite. The interaction between the nanoscale second phase and moving dislocations increases the strength of the composite, but improving wear resistance requires micron- or even millimeter-scale reinforcing phases to resist wear. Excessively fine reinforcing phases may agglomerate or cause compositional segregation in the matrix, which will weaken the mechanical properties and tribological properties of the composite. Oxide ceramic particles have excellent mechanical properties and can be used as one of the most widely used reinforcing phases, but their poor electrical conductivity makes it difficult to meet the requirements of conductive service conditions. Boride ceramics have high hardness while also possessing good electrical conductivity, and can replace oxides as a potential reinforcing phase for copper-based composites.
[0003] Therefore, based on age-strengthened and second-phase-strengthened materials, the design and development of multi-scale boride ceramic particle-reinforced copper-based composite materials with high strength, high conductivity, and high wear resistance has significant engineering value for the rapid development of sliding electronic connectors in rail transit systems and aerospace fields. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to address the shortcomings of the prior art by providing a copper matrix composite material reinforced with dual-phase boride ceramic particles, its preparation method and application. By controlling the proportion of multi-scale boride ceramic particles, determining the preparation process parameters of the composite material and matching its strength, conductivity and wear performance, the invention solves the technical problem of the difficulty in uniformly combining multi-phase and multi-scale ceramic particles in a copper matrix.
[0005] The present invention adopts the following technical solution:
[0006] A method for preparing a copper-based composite material reinforced with biphase boride ceramic particles involves adjusting the ratio of TiB2 to MoB2 ceramic particles and then performing high-energy ball milling to obtain a mixed powder.
[0007] After uniformly mixing copper-titanium alloy with mixed powder of different contents, the mixture is placed in a graphite mold and a composite material preform is prepared by spark plasma sintering technology. The composite material preform is then subjected to solution treatment and aging heat treatment.
[0008] Finally, electron beam remelting technology was used to form a gradient hardening layer on the surface of the composite material preform to obtain a copper-based composite material reinforced with biphase boride ceramic particles.
[0009] Preferably, the mass ratio of TiB2 to MoB2 ceramic particles is (1-3):(3-1).
[0010] More preferably, the high-energy ball milling treatment specifically includes:
[0011] TiB2 ceramic particles of 20–60 μm and MoB2 ceramic particles of 100–500 nm were subjected to vacuum ball milling with 5–40 wt.% copper-titanium alloy powder. The grinding balls were corundum balls, the ball-to-material ratio was (10–5):1, the total ball milling time was 5–10 h, with a 15 min break every 30 min, and 2–5 wt.% alcohol was added during the ball milling process.
[0012] Preferably, the preparation of the composite material preform using spark plasma sintering technology specifically involves:
[0013] The mixed powder is placed in a graphite mold with a diameter of 10–60 mm, and the vacuum degree is maintained at 1–5 × 10⁻⁶ mm. -3 At a pressure of 10-50 MPa, the material is sintered at 750-950℃ for 10-30 minutes and then cooled in the furnace after the heat treatment is completed, forming a preform of copper-based composite material reinforced with dual-phase boride ceramic particles.
[0014] Preferably, the solution treatment temperature is 650–750°C, and the solution treatment time is 2–5 hours.
[0015] Preferably, the aging heat treatment temperature is 350–500℃ and the time is 2–6 hours.
[0016] Preferably, the remelting temperature of the electron beam remelting technology is 900-1100℃, and the scanning speed of the electron beam during the selective remelting process is controlled to be 2-5m / s, the scanning spacing is 0.01-0.05mm, and the scanning power is 200-600W.
[0017] More preferably, before using electron beam remelting technology, the material is preheated at a temperature of 200–300°C.
[0018] Another technical solution of the present invention is a copper-based composite material reinforced with dual-phase boride ceramic particles.
[0019] Another technical solution of the present invention is that a copper-based composite material reinforced with dual-phase boride ceramic particles is applied to high-strength, high-conductivity, and wear-resistant parts.
[0020] Compared with the prior art, the present invention has at least the following beneficial effects:
[0021] This invention discloses a method for preparing a copper-based composite material reinforced with biphase boride ceramic particles. Low-speed, long-term rotation in a planetary ball mill coats the surface of the ceramic particles with metal powder, resulting in uniform mixing of the ceramic and metal powders. Wet mixing absorbs the heat generated during the ball milling process, preventing oxidation of the copper-titanium alloy powder and maintaining its high purity. Spark plasma sintering possesses the unique property of sintering powders under pressure. Furthermore, applying pressure during sintering helps lower the sintering temperature of the mixed powders, effectively preventing excessively coarse grains in the metal matrix during solid-phase sintering of the composite material. Solution treatment allows excess metal atoms to dissolve and distribute uniformly within the matrix, improving the strength of the copper matrix. Subsequent aging treatment causes supersaturated metal atoms to precipitate as a second phase within the matrix, increasing its conductivity. Electron beam remelting technology induces interfacial reactions between the ceramic particles and the copper matrix, aiming to achieve synergistic optimization of the surface microstructure.
[0022] Furthermore, before preparing the composite material by discharge plasma sintering, the two ceramic particles were pre-ball milled. This is mainly because both reinforcing ceramics are irregular particles formed after being crushed by a grinder, and too many sharp points are not conducive to the bonding between the ceramic and the copper matrix.
[0023] Furthermore, nanoscale ceramic particles are prone to agglomeration, resulting in uneven distribution in the matrix. During ball milling, the metal powder undergoes plastic deformation and coats the surface of the ceramic particles. During sintering, the metal powder can more easily control the distribution between particles of different sizes.
[0024] Furthermore, during sintering, in order to prevent the graphite mold and indenter from affecting the sample's microstructure and composition, boron nitride is coated on the surface of the mold before the mixed powder is loaded into the graphite mold, which also facilitates demolding after sintering.
[0025] Furthermore, the determination of the heat treatment process has a significant impact on the microstructure and phase composition of the copper matrix. Combining solution treatment and aging treatment allows the copper matrix to maintain good electrical conductivity while achieving high strength.
[0026] Furthermore, the electron beam sweeps the sample surface multiple times, causing the metal matrix to remelt. The liquid metal fills the delamination and gaps at the interface between the composite matrix and ceramic particles, while maintaining the distribution of biphase ceramic particles in the surface layer of the composite material. Preheating the composite material before surface strengthening can effectively reduce the risk of deformation and cracking.
[0027] A dual-phase boride ceramic particle-reinforced copper-based composite material exhibits a "hard surface, tough core" structure. Encapsulating metal powder on the surface of the ceramic particles facilitates bonding between the ceramic particles and the metal matrix. Heat treatment enhances the composite material's toughness and strength. Electron beam remelting technology is employed to strengthen the material's surface without altering the alloy composition, achieving a metallurgical bond between the ceramic particles and the metal matrix. This results in a surface-reinforced metal matrix composite material with high hardness and wear resistance. This multi-step preparation method aims to achieve a structurally and functionally integrated design, addressing the technical challenge of simultaneously achieving high wear resistance and high toughness.
[0028] Furthermore, ceramic particle-reinforced copper-based composites are primarily used in sliding electrical connection systems, which requires them to possess excellent strength, conductivity, and wear resistance. Wear is a major cause of failure in sliding electrical contact systems, and higher hardness helps delay surface failure.
[0029] In summary, this invention obtains a copper-based composite material with high strength, high wear resistance, and high electrical conductivity through powder metallurgy, heat treatment, and surface strengthening, thereby achieving metallurgical bonding between two-phase, two-scale boride ceramic particles and a copper matrix.
[0030] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0031] Figure 1 This is a microstructure diagram of the copper-based composite material reinforced with biphase boride ceramic particles according to the present invention. Detailed Implementation
[0032] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0033] Unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined to form new technical solutions.
[0034] Unless otherwise specified, all the technical features and preferred features mentioned herein can be combined to form new technical solutions.
[0035] In this invention, unless otherwise specified, percentage (%) or parts refer to weight percentage or parts relative to the composition.
[0036] Unless otherwise specified, the components or preferred components involved in this invention can be combined with each other to form new technical solutions.
[0037] In this invention, unless otherwise specified, the numerical range "a~b" represents an abbreviation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "6~22" means that all real numbers between "6~22" have been listed in this document, and "6~22" is simply an abbreviation of these numerical combinations.
[0038] The "scope" disclosed in this invention can be in the form of a lower limit and an upper limit, and can be one or more lower limits and one or more upper limits, respectively.
[0039] In this invention, the term "and / or" as used herein refers to any combination of one or more of the associated listed items, as well as all possible combinations, and includes such combinations.
[0040] In this invention, unless otherwise stated, the various reactions or operation steps may be performed sequentially or in a particular order. Preferably, the reaction methods described herein are performed sequentially.
[0041] Unless otherwise stated, the technical and scientific terms used herein have the same meanings as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be used in this invention.
[0042] This invention provides a copper-based composite material reinforced with dual-phase boride ceramic particles, its preparation method, and its application. First, metal powder is ball-milled and coated onto the surface of dual-phase boride ceramic particles, followed by drying the mixed powder in a rotary evaporator. Next, the composite material is prepared by spark plasma sintering. The strength and conductivity of the composite material are improved through solution treatment and aging treatment. Finally, electron beam remelting technology is used to obtain a hardened layer on the material surface, simultaneously improving the interfacial bonding performance between the ceramic particles and the metal matrix, transforming the interfacial bonding mode into metallurgical bonding, thereby improving the wear resistance of the material.
[0043] Please see Figure 1 This invention discloses a method for preparing a copper-based composite material reinforced with dual-phase boride ceramic particles, comprising the following steps:
[0044] S1. Weigh 20-60μm TiB2 and 100-500nm MoB2 in a ratio of 1:3 to 3:1, pour the weighed powder into an alumina ball mill jar, then weigh 5-40wt.% copper-titanium alloy powder. To avoid generating a lot of heat during ball milling, add 2-5wt.% anhydrous alcohol, pre-vacuum the ball mill jar, and ball mill the mixed powder in a planetary ball mill for 5-10 hours, with a 15-minute break every 30 minutes. The ball-to-powder ratio is 10:1 to 5:1. Finally, evaporate the alcohol in a rotary evaporator and dry the powder.
[0045] S2. Inject the dried mixed powder into a graphite mold with a diameter of 10-60 mm. Apply pre-pressure to the mixed powder using upper and lower pressure heads to compact it, preventing the mixed powder from splashing due to excessive pressure during sintering. Wait until the vacuum degree of the cavity reaches 1-5 × 10⁻⁶ mm. -3 Sintering is carried out at a pressure of 10–50 MPa, a current of 1–3 kA, and a voltage of 2–5 V, with a vacuum level maintained at 2 × 10⁻⁶ during operation. -6 Pa, sintering temperature is 750~950℃, sintering time is 10~30min, and cooling is carried out with the furnace;
[0046] S3. The microstructure and structure of the composite material matrix are controlled by solution treatment and aging heat treatment. Solution treatment allows excess Ti atoms to dissolve in the matrix at a temperature of 650–750℃ for 2–5 hours. Aging treatment causes the supersaturated Ti atoms dissolved in the Cu matrix to precipitate as a fine second phase, thereby significantly improving the conductivity of the composite material without significantly reducing its strength. The aging temperature is selected as 350–500℃ and the aging time is 2–6 hours.
[0047] The sintered composite material was heated to 650–750°C in a vacuum quartz tube furnace and held for 2–5 hours. The sample was then cooled in air and placed back into the tube furnace to 350–500°C and held for 2–6 hours, before being cooled in the furnace.
[0048] S4. This invention develops a method for remelting and strengthening the surface of composite materials using selective electron beam melting (SELM). A dense structure is formed in the matrix, with no obvious pores or defects found, and the ceramic particles are tightly bonded to the metal matrix. To further improve the interfacial bonding between the composite reinforcement layer and the inner homogeneous material, the material is preheated before surface strengthening at a temperature of 200–300°C. The remelting temperature during the selective remelting process is controlled at 900–1100°C, and the electron beam scanning speed is 2–5 m / s, the scanning spacing is 0.01–0.05 mm, and the scanning power is 200–600 W.
[0049] Compared to oxide ceramics, boride ceramic particles exhibit excellent electrical conductivity, low mismatch with the copper matrix, and superior mechanical properties, ensuring good interfacial bonding when combined with the copper matrix. The bonding method is metallurgical bonding. Heat treatment can alter the microstructure and phase composition of the metal matrix, further increasing strength and electrical conductivity. Electron beams possess characteristics such as high thermal efficiency, no reflection, high power density, fast scanning speed, vacuum environment, and low residual stress, forming a stable reinforcing layer on the surface of the composite material, thereby improving the wear resistance of the material surface.
[0050] The copper-based composite material reinforced with dual-phase boride ceramic particles prepared by this invention has significantly improved wear resistance through process optimization, and the prepared composite material can be applied to high-strength, high-conductivity, and wear-resistant parts.
[0051] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0052] Example 1
[0053] First, micron-sized TiB2 and nano-sized MoB2 ceramic powders were weighed at a mass ratio of 1:3 and placed together with 35 wt.% copper-titanium alloy powder in a ball mill jar. The mixture was intermittently ball-milled in a planetary ball mill for a total milling time of 5 hours, with a 15-minute pause every 30 minutes. The ball-to-powder ratio was 10:1. Both the ball mill jar and grinding balls were made of corundum, and the alcohol content was 2 wt.%. The mixed powder was then dried using a rotary evaporator. The mixed powder was placed in a 30 mm diameter graphite mold and compacted using upper and lower pressure heads. The graphite mold containing the powder was then fixed in the discharge plasma sintering furnace cavity, and its position was adjusted so that the applied load direction was aligned with the movement direction of the pressure heads. A vacuum was then drawn until the vacuum degree reached 2 × 10⁻⁶. -3 Current is applied starting at a pressure of 10 MPa, with a current of 2 kA and a voltage of 3 V. The vacuum level is maintained at 2 × 10⁻⁶ during operation. -6 The sample was sintered at 750℃ for 10 minutes, followed by furnace cooling. In a vacuum tube furnace, the sample was heated to 700℃ and held for 2 hours. After holding, the sample was removed from the quartz tube and cooled to room temperature. The sample was then held at 350℃ for 3 hours and cooled in the furnace. The sample was preheated to 200℃, and then the surface was strengthened using selective electron beam remelting (SEBRT). The scanning speed of the electron beam was controlled at 3 m / s, the scanning interval at 0.05 mm, and the scanning power at 600 W during SEBRT. This yielded a composite material with high strength, high conductivity, and high wear resistance.
[0054] Please see Figure 1The biphase boride-reinforced copper matrix composite material prepared using the above process has micron-scale TiB2 uniformly distributed, while nano-scale MoB2 ceramic particles are distributed around the TiB2 ceramic particles. Both types of ceramic particles are tightly bonded to the copper matrix, and no obvious defects were found. This is mainly because the bonding mode between the ceramic particles and the copper matrix has been transformed into metallurgical bonding.
[0055] Friction tests were conducted on the composite material obtained above. The friction method was upper pin and lower plate, the friction pair was GCr15, and the friction time was 30 min. After friction wear, the sample was ultrasonically cleaned in alcohol for 15 min, dried, and weighed on a precision balance. The average loss rate was 0.02869 g.
[0056] Example 2
[0057] First, micron-sized TiB2 and nano-sized MoB2 ceramic powders were weighed at a mass ratio of 1:3 and placed together with 35 wt.% copper-titanium alloy powder in a ball mill jar. The mixture was intermittently ball-milled in a planetary ball mill for a total milling time of 5 hours, with a 15-minute pause every 30 minutes. The ball-to-powder ratio was 10:1. Both the ball mill jar and grinding balls were made of corundum, and the alcohol content was 2 wt.%. The mixed powder was dried using a rotary evaporator. The mixed powder was then placed in a 30 mm diameter graphite mold and compacted using upper and lower pressure heads. The graphite mold containing the powder was then fixed in the discharge plasma sintering furnace cavity, and its position was adjusted so that the applied load direction was aligned with the movement direction of the pressure heads. A vacuum was then drawn until the vacuum degree reached 2 × 10⁻⁶. -3 Current is applied starting at a pressure of 10 MPa, with a current of 2 kA and a voltage of 3 V. The vacuum level is maintained at 2 × 10⁻⁶ during operation. -6 The sample was sintered at 800℃ for 10 minutes, followed by furnace cooling. In a vacuum tube furnace, the sample was heated to 700℃ and held for 2 hours. After holding, the sample was removed from the quartz tube and cooled to room temperature. The sample was then held at 350℃ for 3 hours and cooled in the furnace. The sample was preheated to 200℃, and then the surface was strengthened using selective electron beam remelting (SEBRT). The electron beam scanning speed was controlled at 3 m / s, the scanning interval at 0.05 mm, and the scanning power at 600 W during SEBRT. This yielded a composite material with high strength, high conductivity, and high wear resistance.
[0058] Friction tests were conducted on the composite material obtained above. The friction method was upper pin and lower plate, the friction pair was GCr15, and the friction time was 30 min. After friction wear, the sample was ultrasonically cleaned in alcohol for 15 min, dried, and weighed on a precision balance. The average loss rate was 0.02643 g.
[0059] Example 3
[0060] First, micron-sized TiB2 and nano-sized MoB2 ceramic powders were weighed at a mass ratio of 1:3 and placed together with 35 wt.% copper-titanium alloy powder in a ball mill jar. The mixture was intermittently ball-milled in a planetary ball mill for a total milling time of 5 hours, with a 15-minute pause every 30 minutes. The ball-to-powder ratio was 10:1. Both the ball mill jar and grinding balls were made of corundum, and the alcohol content was 2 wt.%. The mixed powder was dried using a rotary evaporator. The mixed powder was then placed in a 30 mm diameter graphite mold and compacted using upper and lower pressure heads. The graphite mold containing the powder was then fixed in the discharge plasma sintering furnace cavity, and its position was adjusted so that the applied load direction was aligned with the movement direction of the pressure heads. A vacuum was then drawn until the vacuum degree reached 2 × 10⁻⁶. -3 Current is applied starting at a pressure of 10 MPa, with a current of 2 kA and a voltage of 3 V. The vacuum level is maintained at 2 × 10⁻⁶ during operation. -6 The sample was sintered at 850℃ for 10 minutes, followed by furnace cooling. In a vacuum tube furnace, the sample was heated to 700℃ and held for 2 hours. After holding, the sample was removed from the quartz tube and cooled to room temperature. The sample was then held at 350℃ for 3 hours and cooled in the furnace. The sample was preheated to 200℃, and then the surface was strengthened using selective electron beam remelting (SEBRT). The scanning speed of the electron beam was controlled at 3 m / s, the scanning interval at 0.05 mm, and the scanning power at 600 W during SEBRT. This yielded a composite material with high strength, high conductivity, and high wear resistance.
[0061] Friction tests were conducted on the composite material obtained above. The friction method was upper pin and lower plate, the friction pair was GCr15, and the friction time was 30 min. After friction wear, the sample was ultrasonically cleaned in alcohol for 15 min, dried, and weighed on a precision balance. The average loss rate was 0.03158 g.
[0062] Example 4
[0063] First, micron-sized TiB2 and nano-sized MoB2 ceramic powders were weighed at a mass ratio of 1:3 and placed together with 35 wt.% copper-titanium alloy powder in a ball mill jar. The mixture was intermittently ball-milled in a planetary ball mill for a total milling time of 5 hours, with a 15-minute pause every 30 minutes. The ball-to-powder ratio was 10:1. Both the ball mill jar and grinding balls were made of corundum, and the alcohol content was 2 wt.%. The mixed powder was dried using a rotary evaporator. The mixed powder was then placed in a 30 mm diameter graphite mold and compacted using upper and lower pressure heads. The graphite mold containing the powder was then fixed in the discharge plasma sintering furnace cavity, and its position was adjusted so that the applied load direction was consistent with the movement direction of the pressure heads. A vacuum was then drawn until the vacuum degree reached 2 × 10⁻⁶. -3 Current is applied starting at a pressure of 10 MPa, with a current of 2 kA and a voltage of 3 V. The vacuum level is maintained at 2 × 10⁻⁶ during operation. -6The sample was sintered at 950℃ for 10 minutes, followed by furnace cooling. In a vacuum tube furnace, the sample was heated to 700℃ and held for 2 hours. After holding, the sample was removed from the quartz tube and cooled to room temperature. The sample was then held at 350℃ for 3 hours and cooled in the furnace. The sample was preheated to 200℃, and then the surface was strengthened using selective electron beam remelting (SEBRT). The scanning speed of the electron beam was controlled at 3 m / s, the scanning spacing at 0.05 mm, and the scanning power at 600 W during SEBRT. This yielded a composite material with high strength, high conductivity, and high wear resistance.
[0064] Friction tests were conducted on the composite material obtained above. The friction method was upper pin and lower plate, the friction pair was GCr15, and the friction time was 30 min. After friction wear, the sample was ultrasonically cleaned in alcohol for 15 min, dried, and weighed on a precision balance. The average loss rate was 0.03591 g.
[0065] Example 5
[0066] First, micron-sized TiB2 and nano-sized MoB2 ceramic powders were weighed at a mass ratio of 1:3 and placed together with 5 wt.% copper-titanium alloy powder in a ball mill jar. The mixture was intermittently ball-milled in a planetary ball mill for a total milling time of 5 hours, with a 15-minute pause every 30 minutes. The ball-to-powder ratio was 10:1. Both the ball mill jar and grinding balls were made of corundum, and the alcohol content was 2 wt.%. The mixed powder was dried using a rotary evaporator. The mixed powder was then placed in a 10 mm diameter graphite mold and compacted using upper and lower pressure heads. The graphite mold containing the powder was then fixed in the discharge plasma sintering furnace cavity, and its position was adjusted so that the applied load direction was aligned with the movement direction of the pressure heads. A vacuum was then drawn until the vacuum degree reached 1 × 10⁻⁶. -3 Current is applied starting at a pressure of 10 MPa, with a current of 1 kA and a voltage of 2 V. The vacuum level is maintained at 2 × 10⁻⁶ during operation. -6 The sample was sintered at 750℃ for 10 minutes, followed by furnace cooling. In a vacuum tube furnace, the sample was heated to 650℃ and held for 2 hours. After holding, the sample was removed from the quartz tube and cooled to room temperature. The sample was then held at 350℃ for 2 hours and cooled in the furnace. The sample was preheated to 200℃, and then the surface was strengthened using selective electron beam remelting (SEBRT). The scanning speed of the electron beam was controlled at 2 m / s, the scanning spacing at 0.01 mm, and the scanning power at 200 W during SEBRT. This yielded a composite material with high strength, high conductivity, and high wear resistance.
[0067] Friction tests were conducted on the composite material obtained above. The friction method was upper pin and lower plate, the friction pair was GCr15, and the friction time was 30 min. After friction wear, the sample was ultrasonically cleaned in alcohol for 15 min, dried, and weighed on a precision balance. The average loss rate was 0.03942 g.
[0068] Example 6
[0069] First, micron-sized TiB2 and nano-sized MoB2 ceramic powders were weighed at a mass ratio of 3:1 and placed together with 40 wt.% copper-titanium alloy powder in a ball mill jar. The mixture was intermittently ball-milled in a planetary ball mill for a total milling time of 10 hours, with a 15-minute pause every 30 minutes. The ball-to-powder ratio was 5:1. Both the ball mill jar and grinding balls were made of corundum, and the alcohol content was 5 wt.%. The mixed powder was dried using a rotary evaporator. The mixed powder was then placed in a 60 mm diameter graphite mold and compacted using upper and lower pressure heads. The graphite mold containing the powder was then fixed in the discharge plasma sintering furnace cavity, and its position was adjusted so that the applied load direction was consistent with the movement direction of the pressure heads. A vacuum was then drawn until the vacuum degree reached 5 × 10⁻⁶. -3 Current is applied starting at a pressure of 50 MPa, with a current of 3 kA and a voltage of 5 V. The vacuum level is maintained at 2 × 10⁻⁶ during operation. -6 The sample was sintered at 950℃ for 30 minutes, followed by furnace cooling. In a vacuum tube furnace, the sample was heated to 750℃ and held for 5 hours. After holding, the sample was removed from the quartz tube and cooled to room temperature. The sample was then held at 500℃ for 6 hours and cooled in the furnace. The sample was preheated to 300℃, and then the surface was strengthened using selective electron beam remelting (SEBRT). The scanning speed of the electron beam was controlled at 5 m / s, the scanning interval at 0.05 mm, and the scanning power at 600 W during SEBRT. This yielded a composite material with high strength, high conductivity, and high wear resistance.
[0070] Friction tests were conducted on the composite material obtained above. The friction method was upper pin and lower plate, the friction pair was GCr15, and the friction time was 30 min. After friction wear, the sample was ultrasonically cleaned in alcohol for 15 min, dried, and weighed on a precision balance. The average loss rate was 0.03884 g.
[0071] In summary, this invention provides a dual-phase boride ceramic particle-reinforced copper-based composite material, its preparation method, and its application. The resulting copper-based composite material exhibits excellent wear resistance due to the tight bonding between the ceramic particles and the metal matrix interface layer, forming a metallurgical bond. Therefore, the composite material obtained by this patent can significantly extend the service life of wear-resistant components.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a copper-based composite material reinforced with dual-phase boride ceramic particles, characterized in that, The ratio of TiB2 to MoB2 ceramic particles was adjusted and high-energy ball milling was performed to obtain a mixed powder. The mass ratio of TiB2 to MoB2 ceramic particles was (1~3):(3~1). After uniformly mixing copper-titanium alloy with mixed powder of different contents, the mixture is placed in a graphite mold and a composite material preform is prepared by spark plasma sintering technology. The composite material preform is then subjected to solution treatment and aging heat treatment. Finally, electron beam remelting technology was used to form a gradient hardening layer on the surface of the composite material preform to obtain a copper-based composite material reinforced with biphase boride ceramic particles.
2. The method for preparing dual-phase boride ceramic particle-reinforced copper-based composite material according to claim 1, characterized in that, The high-energy ball milling process specifically involves: TiB2 ceramic particles of 20-60 μm and MoB2 ceramic particles of 100-500 nm were subjected to vacuum ball milling with 5-40 wt.% copper-titanium alloy powder. The grinding balls were corundum balls with a ball-to-material ratio of (10-5):
1. The total ball milling time was 5-10 h with a 15 min break every 30 min. 2-5 wt.% alcohol was added during the ball milling process.
3. The method for preparing dual-phase boride ceramic particle-reinforced copper-based composite material according to claim 1, characterized in that, The specific steps for preparing composite material preforms using spark plasma sintering technology are as follows: The mixed powder is placed in a graphite mold with a diameter of 10~60 mm, and the vacuum degree is maintained at 1~5×10⁻⁶ mm. -3 At a pressure of 10-50 MPa, the material is sintered at 750-950°C for 10-30 min, and then cooled in the furnace after the heat treatment is completed to form a preform of copper-based composite material reinforced with dual-phase boride ceramic particles.
4. The method for preparing dual-phase boride ceramic particle-reinforced copper-based composite material according to claim 1, characterized in that, The solution treatment temperature is 650~750 °C, and the solution treatment time is 2~5 h.
5. The method for preparing dual-phase boride ceramic particle-reinforced copper-based composite material according to claim 1, characterized in that, The aging heat treatment temperature is 350~500 °C, and the time is 2~6 h.
6. The method for preparing dual-phase boride ceramic particle-reinforced copper-based composite material according to claim 1, characterized in that, The remelting temperature of electron beam remelting technology is 900~1100 °C. The scanning speed of the electron beam during the selective remelting process is controlled at 2~5 m / s, the scanning spacing is 0.01~0.05 mm, and the scanning power is 200~600 W.
7. The method for preparing dual-phase boride ceramic particle-reinforced copper-based composite material according to claim 1, characterized in that, Before using electron beam remelting technology, the material is preheated at a temperature of 200~300 °C.
8. A dual-phase boride ceramic particle-reinforced copper-based composite material prepared by the method according to any one of claims 1 to 7.
9. The dual-phase boride ceramic particle reinforced copper matrix composite material according to claim 8 is applied to high-strength, high-conductivity, and wear-resistant parts.
Citation Information
Patent Citations
Titanium carbide and titanium diboride double-phase enhanced copper-based composite material and preparation method thereof
CN107586987A
Preparation method of micro-nano hybrid TiC-TiB2 particle reinforced high-performance aluminum alloy
CN108018442A